Identification and characterization of two new 5-keto-4-deoxy-D-Glucarate Dehydratases/Decarboxylases. Issue 1 (December 2016) - Pick, André; Beer, Barbara; Hemmi, Risa; Momma, Rena; Schmid, Jochen; Miyamoto, Kenji; Sieber, Volker
Abstract Background Hexuronic acids such as D-galacturonic acid and D-glucuronic acid can be utilized via different pathways within the metabolism of microorganisms. One representative, the oxidative pathway, generates α-keto-glutarate as the direct link entering towards the citric acid cycle. The penultimate enzyme, keto-deoxy glucarate dehydratase/decarboxylase, catalyses the dehydration and decarboxylation of keto-deoxy glucarate to α-keto-glutarate semialdehyde. This enzymatic reaction can be tracked continuously by applying a pH-shift assay. Results Two new keto-deoxy glucarate dehydratases/decarboxylases (EC 4.2.1.41) fromComamonas testosteroni KF-1 andPolaromonas naphthalenivorans CJ2 were identified and expressed in an active form usingEscherichia coli ArcticExpress(DE3). Subsequent characterization concerningK m, k cat and thermal stability was conducted in comparison with the known keto-deoxy glucarate dehydratase/decarboxylase fromAcinetobacter baylyi ADP1. The kinetic constants determined forA. baylyi wereK m 1.0 mM, k cat 4.5 s−1, forC. testosteroni K m 1.1 mM, k cat 3.1 s−1, and forP. naphthalenivorans K m 1.1 mM, k cat 1.7 s−1 . The two new enzymes had a slightly lower catalytic activity (increasedK m and a decreasedk cat ) but showed a higher thermal stability than that ofA. baylyi . The developed pH-shift assay, using potassium phosphate and bromothymol blue as the pH indicator, enables a direct measurement. The use of crude extracts did not interfere with the assay and was tested for wild-type landscapes for all three enzymes. Conclusions By establishing a pH-shift assay, an easy measurement method for keto-deoxy glucarate dehydratase/decarboxylase could be developed. It can be used for measurements of the purified enzymes or using crude extracts. Therefore, it is especially suitable as the method of choice within an engineering approach for further optimization of these enzymes.